PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN - Hendra Gunawan (BJRM (Bongaya Journal of Research in Management), 2018)
Humans will tend to experience stress if they are less able to adjust between the desire and the reality, both the reality inside and outside themselves. One of the effects of psychological stress is that it can reduce employee job satisfaction where job satisfaction is a pleasant emotional attitude and loves the job. Employee performance is directly related to the productivity and success of the company in achieving its goals. Employee performance is the result or impact of individual activities over a certain period of time. Employees who have good performance can help the company to achieve agreed goals. The purpose of this study is to analyze the effect of work stress on employee performance at PT. Semen Bosowa Maros. This study uses primary and secondary data. The population of this study were all employees of Human Resources Department & General Affair at PT. Semen Bosowa Maros. Data collection is done by observation and interview. In determining the respondents conducted by purposive sampling method. The analysis used is a single regression analysis. The results of the study showed that job stress had a significant effect on employee performance on employees of PT. Semen Bosowa Maros, while the relationship (correlation) of work stress with employee performance is categorized as strong enough.